DESAIN MODEL MANAJEMAN PELANGGAN USAHA MIKRO KECIL DAN MENENGAH BATIK WARNA ALAM TEMANGGUNG - Supaya, Sandi; Suwardi, Suwardi; Mardinawati, Mardinawati (Politeknik Negeri Semarang, 2017)
The purpose of this research is to develop a model of internationalization of customermanagement, with the specific objective to produce a customer management model that can beimplemented to confront ASEAN Economic Community (MEA) competitors. The output of thisresearch is the Customer Management Model that can be used as a guide to problem abstractionlogic, and guidance in making policies about product offer, price, service, and distribution,scientific articles, teaching materials on customer relationship management courses. Data werecollected from the owner and manager of natural color batik by using survey method. Naturalcolor batik is batik product which in its coloring process does not use chemical substance, butnatural dye from rural environment. Natural dyes from the heart of banana, mahogany, cashewleaf, mango leaves, indigo plants, jengkol skin, teak leaves, red onion leaf, jackfruit wood,rambutan fruit peel. Based on the analysis is concluded that customer life cycle and form ofcompetitive understanding of MEA 2015 become the determinant of customer managementmodel. Prospect stage, First Purchase Stage, Repeat Purchase Stage, and Main Purchase Stageis valid and reliable as the construct of the customer lifecycle variable. In the customer life cycle,the primary customer stage has the highest correlation, and the prospect stage has the lowestcorrelation. The 2015 MEA competition is seen as a form of competition to improve the quality,product competitiveness, and productivity.